Tuning biological activity in dinuclear Cu (II) complexes derived from pyrazine ligands: Structure, magnetism, catecholase, antimicrobial, antibiofilm, and antibreast cancer activity. (23rd April 2021) - Ahmad, Mohammad Shahwaz; Khalid, Mohd; Khan, Mohammad Shahnawaz; Shahid, Mohammad; Ahmad, Musheer; Saeed, Haris; Owais, Mohammad; Ashafaq, Mo
Abstract : In a thrust to establish a structure–activity relationship of dinuclear Cu (II) complexes for derived biological activities, two complexes bearing composition [Cu2 (pza)2 (2‐methoxybenzoate)4 ] (1 ) and [Cu2 (pza)2 (3‐methoxybenzoate)4 ] (2 ) are designed. The complexes are characterized thoroughly via single crystal X‐ray diffraction (XRD), spectroscopic, and magnetic analysis. The exact structure of complexes was elucidated as dinuclear bridged by carboxylates with Cu (II) in each complex present in a distorted square‐pyramidal geometry. The ortho and meta substituted benzoates are used in order to investigate its effect on catecholase and other biological activities. The magnetic data on variable temperature dispense the presence of moderate antiferromagnetic interactions in both the complexes with J = −88.7(2) cm −1, R = 2.13 × 10 −4 for 1 and J = −86.3(2) cm −1, R = 3.11 × 10 −4 for 2 (g = 2.0). As corroborated from UV–visible titrations, cyclic voltammetry (CV), and Electron paramagnetic resonance (EPR) data, the 2 shows enhanced catecholase activity due to higher redox‐active Cu (II) center in 2, which is directly related to the inductive effect of the methoxy substituent. Both the complexes were screened against some bacteria and fungi, and 2 has shown potent activity Escherichia coli . Moreover, the complexes have also shown better antibiofilm properties as compared to their parent salts. The excellent antibreast cancer activity has been observed against MCF‐7 cell line and, 2 has greater IC50 (lower activity) than 1 . Thus, a structure–activity relationship can further direct us to design other substituted complexes with enhanced biological activity in the future course. Abstract : Two new Cu (II) complexes are characterized and exploited for the anti‐breast cancer properties.